Perbedaan Tingkat Depresi antara Lansia yang Tinggal bersama Keluarga di Dusun Diro dengan Lansia di Panti Sosial Tresna Werdha Yogyakarta Unit Budi Luhur - Dicky Budi Nurcahya; . Suparman; Lilik Wijayanti (Nexus Kedokteran Komunitas, 2013)
Background: The population of elders is gradually increasing. The United Nation stated that the elders population is increasing around 77,37% during 2005 till 2025 and Indonesia is the country which is contribute to the high number of its percentage. Depression is a psychiatric disorder that most commonly occurs to the elders. The place where they are living is one factor that may lead to the depression. Some elders are residing in the home with his family and some others are residing within a nursing house. This study is aimed to determine the differences in rates of depression between the elders who living with a family in Diro Village and elders who staying in Tresna Werdha Nursing House the unit of Budi Luhur, Yogyakarta. The study is expected to provide useful input to family members and nursing staff about the psychological condition of the elders. Methods: This study was observational analytic cross-sectional approach. The subjects were elders in Diro village and Tresna Werdha Nursing House the unit of Budi Luhur, Yogyakarta that met the inclusion criteria and were willing to answer the questionnaire study. Depression scores measured using the GDS-SF. Sampling is done by simple random sampling. Data obtained in a total of 35 samples in Diro Village and 35 samples in Tresna Wredha Nursing House the unit of Budi Luhur, Yogyakarta. Samples were then analyzed by unpaired t test using Statistical Product and Service Solutions (SPSS) 17.0 for Window. Results: Data differences in rates of depression between elders living with a family in Diro Village and those living in Tresna Werdha Nursing House the unit of Budi Luhur, Yogyakarta tested by unpaired t test, it was found p = 0,028 (p < 0,05). Conclusions: There were significant differences between the rates of depression in elders living with a family in the Diro Village and Tresna Werdha Nursing House the unit of Budi Luhur, Yogyakarta with p = 0,028 (p < 0,05). Keywords: elders, depression, GDS-SF